Thermodynamic analysis of a direct expansion solar assisted heat pump water heater - Masoud Yousefi; Misagh Moradali (Journal of Energy in Southern Africa, 2017)
In this paper, the thermodynamic performance of a direct expansion solar assisted heat pump (DX-SAHP), which is used to heat domestic water from 20˚C to 45˚C, is theoretically investigated. The system includes a 3m2 single-cover flat plate solar collector, 0.150m3 water tank and 70m tube immersed in the water tank as a condenser. The effect of various parameters such as radiation on the collector surface, compressor speed and the ambient temperature on the coefficient of performance (COP) are calculated. Results show that obtained COP is considerably more than that of a conventional heat pump water heater when radiation on the collector is high. Also, increasing collector area and reducing compressor speed enhance COP. The same occurs when the ambient temperature increases. For instance, at an ambient temperature of 15˚C and 450 w/m2 irradiation on collector surface, the calculated COP was 6.37.